HUBUNGAN SPRINT DAN KEMAMPUAN VERTICAL JUMP PADA PEMAIN BASKET MADRASAH ALIYAH NEGERI 4 JAKARTA - Nadya Ariella Meilianisa (2022)
Recently, research on sports regarding the performance of athletes, especially on basketball teams, is growing rapidly, and quite a lot of research has been carried out throughout the country. Basketball players need good aerobic capacity to be able to recover as quickly as possible from intense action, besides that the game of basketball is also largely dependent on anaerobic metabolism. Because most basketball games rely on jumping and running with high intensity. This study aims to determine the correlation between the sprint and the vertical jump ability of basketball players at Madrasah Aliyah Negeri 4 Jakarta. The research method used by the author is a cross-sectional study. A total of 30 (n = 30) beginner basketball players (mean: age = 15 - 17 years; height = 150 - 180 cm; weight = 50 - 80 kg) were willing to participate in this study. The 30m sprint test becomes a parameter for measuring sprints and countermovement jumps (CMJ) to assess the vertical jump ability. The results of this study showed that of the 30 respondents in the sprint category, the very good category became the largest number with a percentage of 53.3% and in the vertical jump the poor category became the largest number with a percentage of 40.0%. Based on the results of the correlation test using the Pearson product moment, the results of the Pearson correlation r = -520 are not in the same direction. In the results of this study, it was concluded that there was a significant correlation between sprint and vertical jump abilities in basketball players at Madrasah Aliyah Negeri 4 Jakarta with a moderate degree of correlation.